LA ACTIVIDAD FÍSICA Y SU IMPACTO EN LA CONDUCTA SOCIAL (Fiep Bulletin - online, 2024)
Introduction: Physical activity and sport provide psychosocial benefits, improve mood, ability to concentrate and favor the integration of communities, therefore it is important to assess whether sedentary behaviors and lack of physical activity are determined by sociodemographic factors Lavielle-Sotomayor , et al (2014).Objective: Implement the permanent practice of physical activity as a strategy to have an impact on the social fabric. Methods: Type of mixed, correlational and longitudinal research; Where 285 subjects from the Rio Dorado housing unit in Durango Durango participated, (154 men and 231 women) from 8 to 20 years of age, where the exclusion factors were not being an inhabitant of the housing unit or not attending more than 80% to the activities (June to December 2021). Having as main. Results: According to the perception of the subjects, it was evidenced that they have experienced better self-esteem, decreased stress and physical discomfort, better social, neighbor and family relationships, a greater sense of belonging to their community and enjoyment of life, and that they have improved their practices of self care. Conclusion: the practice of physical activity on a permanent basis contributes to a better quality of life, as well as a greater sense of belonging and coexistence in the housing unit.Keywords: Activity Tracker, Healthy Lifestyle, Sociality.